LINGUISTIC EXPERTISE IN HATE SPEECH CASES: PROBABILITY ISSUES - Kmetyk, Khrystyna; Leuska, Olena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of this article is to provide a comprehensive analysis of the problems of evidence substantiation in the process of linguistic expertise in cases related to hate speech, as well as to identify key challenges and determine directions for improving methodological approaches to the analysis of relevant texts in legal practice. Particular attention is paid to the correlation between linguistic and legal criteria for assessing speech acts that may contain signs of discrimination, hostility, or incitement to violence. Research methods: the study employs a set of general scientific and special methods, including semantic-textual analysis to examine the content structure of speech acts, discourse analysis to take into account social, political, and cultural contexts, and a linguopragmatic approach to determine the communicative intent of the author. In addition, the comparative legal method is used to analyse national and international approaches to defining and identifying hate speech. The application of these methods ensures the interdisciplinary nature and consistency of the research. Results: the study reveals that one of the main problems in proving hate speech cases is the lack of unified terminological definitions and standardized procedures for linguistic expertise, which leads to subjectivity in expert conclusions. Significant difficulties arise in distinguishing factual statements from evaluative judgments, as well as in identifying implicit meanings that may acquire provocative or discriminatory characteristics depending on the context. It is established that extralinguistic factors, including the socio-political situation, the type of discourse, and the characteristics of the digital communication environment, play a decisive role in the interpretation of speech acts. Discussion: the findings demonstrate that the effectiveness of linguistic expertise in hate speech cases largely depends on the application of a comprehensive approach combining linguistic, legal, and social criteria for text evaluation. The necessity of standardizing terminology, developing clear identification criteria, and implementing unified analytical procedures is substantiated in order to enhance objectivity and legal accuracy in the process of evidence substantiation.